New Concepts of Dense set in i-Topological space and Proximity Space (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A new kind of some topological spaces concepts has been defined in i-topological spaces with respect to proximity spaces in our paper.